Publicly announced speed limit enforcement and its impact on road safety: Evidence from the German Blitzmarathons - Ramona Molitor (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper studies a unique traffic law enforcement campaign in Germany and its impact on road safety. Key features of the campaign are (1) repeated one-day lasting massive speed limit monitoring (so called Blitzmarathons) and (2) a media campaign that informs the public in advance about the timing, extent, and purpose of the speed limit monitoring. Using administrative records on all police reported vehicle crashes in Germany from 2011 to 2014 and generalized difference-indifferences estimations, we find an eight percent reduction in the number of traffic accidents and a nine percent reduction in the number of slightly injured during Blitzmarathon-day compared to regular days. The effect begins to emerge with the onset of the media campaign, one to three days before a Blitzmarathon. However, while the initiators of the Blitzmarathons intended a permanent change in road safety, we do not find that the reduction in traffic accidents persists beyond a Blitzmarathon-day. In terms of mechanisms, we show that a substitution of traffic from motorized vehicles to other modes of transport not targeted by the Blitzmarathons does not drive our results, and we demonstrate that overall driving speed is lower during a Blitzmarathon-day compared to other days. Given the general relevance of traffic law enforcement strategies, our result have important implications for policy makers beyond the German context.
Keywords: H76; K42; R41; 330; traffic; law enforcement; safety; accidents